Elika, Variable Flow With Fixed Displacement Helical Pump - Persici, Danilo; Rimondi, Andrea (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Electrification and hybridization have reduced engine noise in industrial vehicles, making hydraulic circuit noise the dominant source. Variable displacement pumps can lower noise but often at the cost of efficiency. The Elika gear pump, developed with the University of Bologna, uses patented helical gear technology to deliver low noise and high efficiency across a wide speed range, particularly when paired with Variable Frequency Drive brushless motors. Recent Marzocchi R&D tests showed it can deliver flows from 1 l/min to 20 l/min with the same displacement, maintaining over 90 % volumetric efficiency. These characteristics enable variable flow from a fixed displacement pump, offering a cost-effective, energy-efficient alternative to variable displacement designs, especially for electrified powertrains where noise reduction and efficiency are critical.